Finance fundamentals for nonprofits building capacity and sustainability - Bowman, Woods, 1941- (Wiley nonprofit authority, 2011)
"A complete guide to the financial requirements a nonprofit organization must follow to indefinitely maintain the volume and quality of their servicesAn organization may have plenty of capacity in the long run, but in the short run, donor restrictions and limited financing options are constraining. Here-and-now liquid assets are the only resources available. Finance Fundamentals for Nonprofits: Building Capacity and Sustainability shows how to measure a nonprofit organization's financial capacity in different time frames and how to measure its ability to sustain capacity in each case. Explains how nonprofits differ from businesses and how they promote values-centered management Reveals how to improve financial capacity and sustainability Written by a nonprofit scholar Filled with real-world case studies and actionable advice relating financial health to financial capacity and sustainability, this book is essential reading for every nonprofit professional"--